1990
DOI: 10.1016/0275-5408(90)90003-h
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in reading with closed-circuit television for low vision

Abstract: A closed circuit television (CCTV) magnifier was used to measure the reading rates of nine fluent low-vision subjects. Performance was found to be dependent on field width, character size, and the number of characters displayed in line. A field width of 70 degrees and a mean of 24 characters were commensurate with the fastest reading rate. The optimal character size that elicited the fastest reading was determined for each subject. In seven of the nine subjects, this differed from the character size selected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…The FOV was considered here because past studies (Legge et al, 1985a,b;Lovie-Kitchin and Woo, 1988;Lowe and Drasdo, 1990) were contradictory in their findings. In particular, those by Legge et al (1985a,b) have shown that only 4 characters is sufficient to achieve optimal RR, whilst others have suggested a much larger FOV of 15 (Lovie-Kitchin and Woo, 1988), or 25 to 35 characters (Lowe and Drasdo, 1990). More recently, Beckmann et al suggested that the discrepancies are attributable to the different methods used in the studies (Beckmann et al, 1993;Beckmann and Legge, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FOV was considered here because past studies (Legge et al, 1985a,b;Lovie-Kitchin and Woo, 1988;Lowe and Drasdo, 1990) were contradictory in their findings. In particular, those by Legge et al (1985a,b) have shown that only 4 characters is sufficient to achieve optimal RR, whilst others have suggested a much larger FOV of 15 (Lovie-Kitchin and Woo, 1988), or 25 to 35 characters (Lowe and Drasdo, 1990). More recently, Beckmann et al suggested that the discrepancies are attributable to the different methods used in the studies (Beckmann et al, 1993;Beckmann and Legge, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a field of view (FOV) of 4 characters has been suggested to be sufficient for optimal RR (Legge et al, 1985a,b) but other studies have suggested higher figures (Lovie-Kitchin and Woo, 1988;Lowe and Drasdo, 1990). Since high magnification is achieved at the expense of the FOV, in the present study the FOV of each magnifier was controlled.…”
Section: Introductionmentioning
confidence: 91%
“…Electronic devices offer some advantages as bigger working distance, higher magnification than conventional devices [5,6]. Nevertheless, more training sessions are required in order to improve the use of these kind of devices.…”
Section: Discussionmentioning
confidence: 98%
“…optical magnifiers 2,3 and electronic enhancement systems [4][5][6][7][8][9][10][11] are cosmetically and functionally inadequate for many patients. Surgical alternatives to improve visual acuity, such as implantation of intraocular low-vision devices, have varying results.…”
mentioning
confidence: 99%